2015
DOI: 10.1111/ssm.12132
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Ability of an Online Environment to Facilitate the Critical Features of Teacher Professional Development

Abstract: Providing teachers effective professional development (PD) is an ongoing challenge in the field of education. Emergence of technological innovations in the form of computer‐based asynchronous and synchronous communication has provided new opportunities to improve and expand teacher PD opportunities beyond the physical walls of a school. The purpose of this meta‐analysis is to examine the ability of online learning environments to facilitate the critical features of teacher PD identified in Desimone (2009) as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
(62 reference statements)
0
12
0
1
Order By: Relevance
“…Given the importance of sustained duration and collective participation of teachers identified in models on the effectiveness of TPD (Smith & Sivo, 2012), this study evaluates an innovative OTPD initiative, in the form of a webinar series with a strong collaborative‐learning component. Surrette and Johnson (2015) conducted a meta‐analysis on the ability of OTPD to integrate the critical features for effective TPD as identified by Desimone (2009), and demonstrated that multiple online initiatives were evaluated positively with regard to collaborative‐learning possibilities. In the majority of interventions evaluated, teacher interaction occurred using discussion boards or in chat boxes.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of sustained duration and collective participation of teachers identified in models on the effectiveness of TPD (Smith & Sivo, 2012), this study evaluates an innovative OTPD initiative, in the form of a webinar series with a strong collaborative‐learning component. Surrette and Johnson (2015) conducted a meta‐analysis on the ability of OTPD to integrate the critical features for effective TPD as identified by Desimone (2009), and demonstrated that multiple online initiatives were evaluated positively with regard to collaborative‐learning possibilities. In the majority of interventions evaluated, teacher interaction occurred using discussion boards or in chat boxes.…”
Section: Introductionmentioning
confidence: 99%
“…We located two systematic reviews from the EPPI Center (Cordingely, Bell, Ishams, Evan, & Firth, 2007) and What Works Clearing House (Yoon et al, 2008), one meta-analysis from What Works Clearing House (Yoon et al, 2007), and two other meta-analysis from Psych Info: (Saylor & Johnson, 2014;Surrette & Johnson, 2015). We excluded the two latter meta-analyses from this review because the results were interpreted in a qualitative manner, student data was not reported, and there were no specific foci on literacy.…”
Section: Professional Development Of Teachers and Student Literacymentioning
confidence: 99%
“…It should be stressed that this is an exploratory treatment of the question. While reviews such as Surrette and Johnson (2015) [63] and several other pieces we discuss below provided an excellent starting point, the literature (even when taken as a whole) did not yield an extended or comprehensive account. So, in what follows we draw on our own expertise as well as the studies and reviews in the review database, where these discuss or present relevant principles and issues.…”
Section: Affordances and Limitations Of Remote And Blended Approaches To Teacher Educationmentioning
confidence: 99%
“…Eliot also discusses 'cognitive presence', and 'teaching presence' (p. 118), which refer respectively to how learners interact with the content in the environment, and the instructional design and delivery within the course. Surrette and Johnson's 2015 [63] meta-analysis suggests that it is possible to achieve all of these within an online space. Their analysis of 20 empirical studies (ranging from single-case qualitative studies to randomised controlled trials) indicated that 'online PD that facilitated opportunities for collective participation enabled the teachers to (a) experience a high level of social connection with their peers, (b) engage in multiple opportunities to reflect on their teacher practice and the practice of their peers, (c) share knowledge and experiences with peers, and (d) increase their knowledge and understanding of unique instructional strategies' (Surrette and Johnson, 2015, p. 266) [63].…”
Section: Presence Participation and Facilitationmentioning
confidence: 99%
See 1 more Smart Citation